An Open-Source Multi-Robot Framework System for Collaborative Environments Based on ROS2 - Francisco Yumbla; Marcelo Fajardo-Pruna; Anthonny Piguave; Diego Ronquillo; Ricardo Ortiz; Jongseong Brad Choi; Gabriel Diaz; Xabiel G. Paneda; Hyungpil Moon (IEEE Access, 2025)
Despite the rise of robotics and automation in industrial applications, the widespread adoption of collaborative robotics still needs to be improved due to the lack of interoperability between robots and the low adaptability of existing systems. Solving this problem would mean a significant advance in robotics and industrial automation. Under this context, an open-source MultiRobot Framework based on ROS2 was developed in the present research to effectively communicate and coordinate robotics agents and sensors in closed collaborative environments. A simulation-based control and software design was performed using the GAZEBO tool. A centralized architecture was obtained with an autonomous navigation module for the planning and robot routes monitoring, a computer vision module for the location and management of uncertainties, and a task controller module to assign mobilization mission objects. In conclusion, using ROS2 to communicate and coordinate various mechatronic systems effectively results in a robust, flexible, and scalable solution critical to industrial processes.